2020
DOI: 10.3390/ma13235358
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Treatment on Cyclic Response of Nickel-Based Superalloy Inconel 718 up to Very-High Cycle Regime

Abstract: Cyclic response and fatigue behavior are sensitive to the microstructure of material induced by heat treatment. In this paper, three sets of high-temperature superalloy Inconel 718 with different heat treatment, namely annealed, aged, and directly aged high quality (DAHQ), are compared. Difference in grain size distribution, phase, and precipitate, etc., were investigated using an optical camera and scanning electron microscopy. Yield and ultimate strength were found to increase obviously after aging heat trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…The obtained fatigue life values were compared with the results of the fatigue test at an ambient temperature of about 22 °C ± 5°C, but the loading frequency, in this case, was f = 20,000 kHz. Fatigue failure and fatigue life are affected by several factors such as the formation of oxides, which form at high temperatures at the surface and affect the mechanism of fatigue crack closure by excluding phases such as BCT DO 22 Ni 3 Nb γ″-phase and orthorhombic D0 a Ni 3 Nb δ-phase, as demonstrated in Ling et al [ 64 ]; the frequency of loading and the number of cycles to fracture, as reported by Song et al [ 32 ]; or the heat treatment method, as reported by Zhao et al [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained fatigue life values were compared with the results of the fatigue test at an ambient temperature of about 22 °C ± 5°C, but the loading frequency, in this case, was f = 20,000 kHz. Fatigue failure and fatigue life are affected by several factors such as the formation of oxides, which form at high temperatures at the surface and affect the mechanism of fatigue crack closure by excluding phases such as BCT DO 22 Ni 3 Nb γ″-phase and orthorhombic D0 a Ni 3 Nb δ-phase, as demonstrated in Ling et al [ 64 ]; the frequency of loading and the number of cycles to fracture, as reported by Song et al [ 32 ]; or the heat treatment method, as reported by Zhao et al [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…This load method is more complex and combines bending and tensile load, which corresponds to significantly lower values of fatigue life compared to the classic push–pull load. The obtained results are unique in that most authors [ 32 , 64 , 65 ] have performed fatigue tests either only at ambient temperature and with a low load frequency or with a different parameter of the cycle asymmetry R. The data on increased δ-phase volume fraction and its influence on fatigue life have not been studied up until now. For this reason, we considered the results of high-temperature fatigue and its comparison with the fatigue life obtained at ambient temperature to be unique, especially if they were made on materials with the same grain size and the same processing method (i.e., the effect of changing the grain size), so a different γ′/γ″ phase ratio was eliminated.…”
Section: Resultsmentioning
confidence: 99%
“…The first-stage annealing (FSA) and second-stage annealing (SSA) aim to precipitate the δ phase and promote recrystallization, respectively. Moreover, the strengthening heat treatment (per AMS 5596) was added for all uniaxial tensile specimens to precipitate the strengthen γ′′ and γ′ phases [ 38 , 39 ]. In addition, to investigate the difference of tensile behavior at high temperature and room temperature, cases 3 and 9 in addition to 4 and 10 were annealed in the same condition of annealing but deformed under different tensile tests.…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…In the past four decades, nickel-base superalloys have experienced rapid development and received widespread attention from experts in various fields [ 1 , 2 , 3 ]. Among them, Inconel 718, a typical austenitic superalloy with Ni, Cr, Fe, Mo, Co, Nb as the main elements, has been widely used in the fields such as aeronautics and astronautics, guide vanes, and high-pressure compressor discs in gas turbines due to its excellent comprehensive mechanical properties, sound corrosion resistance and high oxidation resistance under high temperature conditions [ 4 , 5 , 6 ]. With the development of modern industry, new advanced equipment has put forward higher and higher requirements on the shape, structure and performance of components, and the demand for Inconel 718 parts with complex geometries, especially complex internal cavity geometry and porous structure with high dimension precision is becoming more and more urgent.…”
Section: Introductionmentioning
confidence: 99%